Vehicle Dynamics Fundamentals and Ultimate Trends - Lenzo, Basilio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book examines the fundamentals of vehicle dynamics, as well as the recent trends in the field, such as torque vectoring control, vehicle state estimation, and autonomous vehicles. It investigates the most pressing problems that vehicle dynamics engineers have been facing nowadays, and the challenges of autonomous vehicles in terms of perception, path planning, and analysis of the road environment. The book will serve as a useful tool for graduate students and researchers in vehicle dynamics and control.
Fundamentals on Vehicle and Tyre Modelling -- Vehicle Steering and Suspension Kinematics/Compliance and their Relationship to Vehicle Performance -- Tyre Mechanics and Thermal Effects on Tyre Behaviour -- Torque Vectoring Control for Enhancing Vehicle Safety and Energy Effciency -- State and Parameter Estimation for Vehicle Dynamics -- Automated Driving Vehicles.
Keywords: Vehicles; Mechanics, Applied; Control engineering; Automotive engineering; Vehicle Engineering; Engineering Mechanics; Control and Systems Theory; Automotive Engineering; Motor vehicles -- Dynamics; Automated vehicles